2019
DOI: 10.1021/acs.iecr.9b03921
|View full text |Cite
|
Sign up to set email alerts
|

Fouling Diagnosis of Pennsylvania Grade Crude Blended with Opportunity Crude Oils in a Refinery Crude Unit’s Hot Heat Exchanger Train

Abstract: The continual decline in the quantity of legacy Pennsylvania grade crude oil coupled with recent volatile crude oil prices has prompted American Refining Group to start processing a wide variety of opportunity crudes to expand its crude oil feedstock slate to maintain profit margins. As opportunity crude usage increases, crude oil fouling and unexpected corrosion have become major issues in the refinery crude unit's hot heat exchanger train (HHET) and other process units. Crude oil fouling in the refinery has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The fouling mechanism of LTOs is a widely argued question in the industry with a few strong and sometimes contradicting theories. ,− The fractions of LTOs were separated to study their contributions to the fouling potential. LTO-2 was a crude oil with high fouling potential as exhibited in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fouling mechanism of LTOs is a widely argued question in the industry with a few strong and sometimes contradicting theories. ,− The fractions of LTOs were separated to study their contributions to the fouling potential. LTO-2 was a crude oil with high fouling potential as exhibited in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Increased fouling has been observed across refineries processing a significant amount of LTO. , The reason for such an increase in fouling is a lively debated topic. Mechanisms, such as solids and unstable asphaltenes, have been mentioned. Upstream additives have been thoroughly evaluated by NACE International for their downstream impact on fouling and corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio S BN /I N (solubility blending number/insolubility number) was estimated using the information obtained from the n-heptane dilution test [10] and employing Equation (5) [55].…”
Section: Compatibility Indices Based On Petroleum Sara Analysis Datamentioning
confidence: 99%
“…It is well-known that the sediment recovered during the crude oil centrifuging process can be classified as inorganic and organic. Inorganic sediment is represented by suspended impurities, such as sand, dirt, clay, or rust coming from the crude oil production process [13,55]. Organic sediments include asphaltenes, and high molecular waxes [13,55,58].…”
Section: Relations Between Compatibility Indices and Crude Oil Proper...mentioning
confidence: 99%
“…Ho studied five crude oils and found that the fouling propensity depends on compatibility parameters as well as on asphaltene content, total base number (TBN), and metal (Ni and V) contents. More recently, this correlation was used to evaluate fouling propensity of opportunity crude oils in a refinery setting although TBN was replaced by total acid number (TAN) in the correlation. In another study, the fouling of 13 blends of crude oils with different characteristics was studied using a modified ALCOR unit.…”
Section: Introductionmentioning
confidence: 99%